(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
It is the process of protecting systems, networks, and programs against digital attacks. These cyber attacks usually aim to access, alter or destroy sensitive information; For the purpose of extorting money from users or interrupting normal business operations. Implementing cyber security measures is a huge challenge today because there are more devices than people and attackers are becoming more innovative. A successful cyber security approach has multiple layers of protection spread across computers, networks, programs or the data one wants to preserve. People, processes and technology must complement each other within an organization to create an effective defense against cyber attacks